Effects of fluorination and thermal annealing on charge recombination processes in polymer bulk-heterojunction solar cells. Issue 40 (2nd October 2018) - Más-Montoya, Miriam; Li, Junyu; Wienk, Martijn M.; Meskers, Stefan C. J.; Janssen, René A. J.
Abstract : Fluorine substitution and thermal annealing affect the distribution of charge-transfer states and the charge recombination mechanisms of polymer bulk-heterojunction solar cells. Abstract : We investigate the effect of fluorination on the photovoltaic properties of an alternating conjugated polymer composed of 4, 8-di-2-thienylbenzo[1, 2- b :4, 5- b ′]dithiophene (BDT) and 4, 7-bis([2, 2′-bithiophen]-5-yl)-benzo-2-1-3-thiadiazole (4TBT) units in bulk-heterojunction solar cells. The unsubstituted and fluorinated polymers afford very similar open-circuit voltages and fill factor values, but the fluorinated polymer performed better due to enhanced aggregation which provides a higher photocurrent. The photovoltaic performance of both materials improved upon thermal annealing at 150–200 °C as a result of a significantly increased fill factor and open-circuit voltage, counteracted by a slight loss in photocurrent. Detailed studies of the morphology, light intensity dependence, external quantum efficiency and electroluminescence allowed the exploration of the effects of fluorination and thermal annealing on the charge recombination and the nature of the donor–acceptor interfacial charge transfer states in these films.